2019
DOI: 10.1088/2053-1591/ab3bd3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring disorder in the spin gapless semiconductor Mn2CoAl

Abstract: Since the prediction of spin-gapless semiconducting behaviour in the Heusler compound Mn2CoAl, evidence of spin-gapless behaviour in thin films has typically been inferred from magnetotransport measurements. The spin gapless state is however fragile, and further, band structure calculations indicate that even a small amount of atomic disorder may destroy it. To explore the impact of disorder on the properties of Mn2CoAl, we have undertaken an experimental study of the structural, magnetotransport and optical p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…From our previous work, the ferromagnetic Mn 2 CoAl layer shows a positive AHE from 300 K to 5 K [34]. Recently, Basha et al, directly observed that there is an intermixing CoPd alloy in Co 2 MnSi/Pd ultrathin films similar to our system [35].…”
Section: Model Based On Two Magnetic Contributionssupporting
confidence: 78%
See 1 more Smart Citation
“…From our previous work, the ferromagnetic Mn 2 CoAl layer shows a positive AHE from 300 K to 5 K [34]. Recently, Basha et al, directly observed that there is an intermixing CoPd alloy in Co 2 MnSi/Pd ultrathin films similar to our system [35].…”
Section: Model Based On Two Magnetic Contributionssupporting
confidence: 78%
“…With increasing the thickness of the Pd layer, there is more CoPd formed with a stronger negative AHE and μ 0 H CoPd increases so that the total AHE reverses to negative with a peak. Regarding the samples with a thick Pd layer, like t Pd 3.2 nm, most of the electric current will pass through the Pd layer because the bulk resistivity of Pd, ∼11 μ cm [37], is much lower than that of Mn 2 CoAl, 200 μ cm [34], which is the so-called shunting effect. This effect leads to a reduction of the net AHE of the Mn 2 CoAl/Pd bilayer with intermixed CoPd at the interface and a decline of the peak for the samples with a thick Pd layer as shown in Fig.…”
Section: Model Based On Two Magnetic Contributionsmentioning
confidence: 99%
“…Some studies have reported that Mn 2 CoAl is a spin-gapless semiconductor, 20,23,24 while other studies reported that rather Mn 2 CoAl is a half-metal due to its disordered crystal structure. 25−28 It was suggested that antisite defects between Mn and Al exist in thin films, 26,28 and partial substitution of Co for Mn and substitution of Mn for Al are found in bulk samples. 27 It should be noted that in these studies, the measured samples have nonstoichiometric compositions such as Mn 1.7 Co 1.2 Al 1.1 26 and Mn 1.8 Co 1.4 Al 0.8 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…25−28 It was suggested that antisite defects between Mn and Al exist in thin films, 26,28 and partial substitution of Co for Mn and substitution of Mn for Al are found in bulk samples. 27 It should be noted that in these studies, the measured samples have nonstoichiometric compositions such as Mn 1.7 Co 1.2 Al 1.1 26 and Mn 1.8 Co 1.4 Al 0.8 . 27 Such a nonstoichiometry may be the origin of the abovementioned antisite defects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The domain period of demagnetizing image is extracted using a two-dimensional fast Fourier transform by the Gwyddion software [110]. Here, the basic properties of thick Mn 2 CoAl (100 nm) films will be introduced, which have been fully studied by my group [68]. The Mn 2 CoAl thin films are deposited on single-crystalline MgO(001) substrates by the magnetron sputtering with a base pressure below 3×10 −8 Torr.…”
Section: Moke Image Processingmentioning
confidence: 99%